Addressing methodological issues in a study of impulsivity and vulnerability for transition to alcohol use disorder. (14th December 2021) - Poulton, Antoinette; Eastwood, Oliver; Bruns, Loren Richard; Sinnott, Richard O.; Hester, Robert
Abstract: Background: Heightened behavioral impulsivity has been advocated as a preexisting risk factor for the development of alcohol use disorder (AUD). Nonetheless, studies investigating impulsivity in adolescent/young adult at‐risk drinkers—who are at increased risk of developing AUD—report mixed findings. This may be due to methodological limitations related to definitions of at‐risk drinking, the retrospective assessment of alcohol intake, and/or the relatively modest sample size of some studies. Methods: Healthy individuals ( N = 814, M age = 22.50) completed online surveys and a measure of choice impulsivity. Of these, a number of participants also undertook an online measure of response inhibition ( n = 627, M age = 22.66), and a further subgroup submitted real‐time alcohol consumption information for a period of 21 days using an app ( n = 543, M age = 22.96). Differences in behavioral impulsivity were assessed as a function of various at‐risk alcohol intake categories. Hierarchical multiple regression was employed to determine whether impulsivity predicted alcohol use in the form of a continuous index comprising variables related to intake and consequences of use. Results: Significantly greater impulsivity was not evident in heavy, standard binge, high binge, harmful, or hazardous alcohol drinkers as compared to controls, regardless of the criteria employed to categorize these at‐risk drinkers. Neither choice impulsivity nor reduced response inhibition significantly predicted the alcohol use index. Conclusions: While results could be attributed to the online nature of this research, it is possible that more sensitive measures of behavioral impulsivity are required when assessing nondependent drinkers. Abstract : We examined behavioural impulsivity in adolescent/young adult at‐risk drinkers. Online protocols were utilised to facilitate a large sample. Impulsivity differences were assessed as a function of various at‐risk alcohol intake categories. Heightened impulsivity was not evident in heavy, standard binge, high binge, harmful, or hazardous alcohol drinkers, as compared to controls, regardless of criteria employed to categorise these individuals. Impulsivity did not predict elevated alcohol use in the form of an alcohol use index.